Cytoreduction and intraperitoneal heated chemotherapy for the treatment of endometrial carcinoma recurrent within the peritoneal cavity. Issue 1 (1st January 2007) - Helm, C. W.; Toler, C. R.; Martin, R. S.; Gordinier, M. E.; Parker, L. P.; Metzinger, D. S.; Edwards, R. P.
Abstract : Our experience with hyperthermic intraperitoneal chemotherapy (IPHC) in conjunction with surgical resection for endometrial cancer recurrent within the abdominal cavity was reviewed. Eligible patients underwent exploratory laparotomy with the aim of resecting disease to ≤5 mm maximum dimension followed immediately by intraperitoneal perfusion of cisplatin (100 mg/m 2 ) heated to 41–43°C (105.8–109.4°F) for 1.5 h. Data for analysis was extracted from retrospective chart review. Five patients underwent surgery and IPHC between September 2002 and January 2005 for abdomino-pelvic recurrence. Original stage and histology were 1A papillary serous (1), 1C endometrioid with clear cell features (1), and 1B endometrioid (3). Mean age was 61 (41–75) years, mean prior laparotomies were 1.4 (1–2), and mean chemotherapy agent exposure was 1.6 (0–4). Mean time from initial treatment to surgery and IPHC was 47 (29–66) months. Mean length of surgery was 9.8 (7–11) h after which three patients had no residual disease and two had ≤5 mm disease. The mean duration of hospital stay was 12.6 (6–20) days. Postoperative surgical complications included wound infection with septicemia in one patient. Mean maximum postoperative serum creatinine was 1.02 (0.6–1.70) mg/dL. There was no ototoxicity or neuropathy and no perioperative mortality. No patients have been lost to follow-up. Two are living disease free at 28 and 32 m and two are living with disease at 12 and 36 m. One patient died at 3 m without evidence of cancer. Two patients who had no residual macroscopic disease at the end of surgery are alive at 32 and 36 m. The combination of IPHC with surgery for recurrent endometrial carcinoma is relatively well tolerated. The unexpectedly long survival seen in this cohort supports a phase II trial of IPHC with cisplatin for recurrent endometrial cancer.